KEILMIAHAN AYAT-AYAT PENCIPTAAN MANUSIA: Telaah Penafsiran Tantawi Jawhari dalam Tafsir al-Jawahir - Hulami al-Amin; Abdul Rasyid Ridho (el-'Umdah, 2019)
The origin of human creation and biological events is an important study material in the discourse of modern science. Even more so when related to Darwin's theory of human creation which has drawn much debate to this day. So this paper tries to provide a description of the scientific interpretation carried out by Tantawi Jawhari on the verses of human creation shows efforts that lead to rational and progressive interpretations. The rationality of the scientific interpretation of Tantawi Jawhari in the verses of human creation can be seen from its interpretation which reflects an attempt to affirm the religious spirit of a rational, progressive and integrative people. Interpretation of Tantawi Jawhari not only shws the use of reason but reflects progress and unity between the sciences in Islam.